Um Módulo de Monitoramento para uma Arquitetura de Transmissão de Mídia Contínua. - NAHUZ, Sadick Jorge (2008)
The Internet has experienced a considerable increase in the use of audio and video applications, which provoke a large consumption of the resources available in the network and servers. Therefore, the monitoring and analysis of those resources becomes an essential task in order to enhance the service delivered to users. This work depicts a monitoring module implemented in a video server architecture, which is used to track the transmission of some popular video formats. Our experiments have demonstrated that one of the formats delivers a performance considerably better than the other, regarding the bandwidth allocated to each user session, what only reassures the importance of having such a monitoring module available in a server architecture.